Implementasi Problem Based Learning dalam Pembelajaran PAI pada Kurikulum Merdeka di UPTD SDN 52 Panasakkang - Fachrani, Anisa; R, Rosdiana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine and describe the implementation of the Problem Based Learning (PBL) model in Islamic Religious Education (PAI) under the Merdeka Curriculum, as well as its impact on students’ engagement and understanding. This research is a field study using a descriptive qualitative method with a phenomenological approach. Primary data were collected through observation and interviews with the principal and the PAI teacher at UPTD SDN 52 Panasakkang, while secondary data were obtained from journals, theses, and other relevant research documents. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The validity of the data was tested using source and method triangulation. The findings reveal that PBL has been implemented gradually and contextually through group discussions, case studies, and projects that incorporate Islamic values into real-life situations. This model has proven effective in enhancing students’ active participation, critical thinking, and comprehension of Islamic teachings. The implication of this study suggests that PBL is an effective and contextual approach to Islamic education and should be optimized through teacher training and a supportive learning environment.